1984
DOI: 10.1111/j.1365-2230.1984.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of eczema and other dermatoses of the hands and forearms in construction workers in the Netherlands

Abstract: Summary An examination of the hands and forearms of about 1700 construction workers revealed that 133 of them (7.8%) had a form of eczema, whereas psoriasis was observed in twenty‐two (1.3%). Irritant dermatitis was the major diagnostic category and was found in sixty‐seven workers (4%); allergic contact eczema was found in 1.4%. The prevalence of eczema/dermatitis in different job categories varied between 5.9% in technicians and 12.6% in bricklayers and plasterers. A history of atopy was more prevalent in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 5 publications
0
10
1
Order By: Relevance
“…Only 2 cases (0.26%) of psoriasis were seen, which is less than the prevalence of 1.3 % found in similar investigations elsewhere (10). Allowing for the fact that only the hands and arms (elbows) were examined, this finding is supported by circumstantial evidence that psoriasis has a much lower prevalence (0.3%) in the mongoloid race (11).…”
Section: Discussionmentioning
confidence: 56%
“…Only 2 cases (0.26%) of psoriasis were seen, which is less than the prevalence of 1.3 % found in similar investigations elsewhere (10). Allowing for the fact that only the hands and arms (elbows) were examined, this finding is supported by circumstantial evidence that psoriasis has a much lower prevalence (0.3%) in the mongoloid race (11).…”
Section: Discussionmentioning
confidence: 56%
“…This is the first study focusing on doctor-diagnosed CD among construction workers in the Netherlands in more than 25 years. 44 Recently, we reported high prevalences of selfreported skin symptoms 3 and self-reported CD. 4 However, the current study was not confined to self-reported data.…”
Section: Discussionmentioning
confidence: 97%
“…2 methods have been used to diagnose hand eczema in questionnaire studies: a self‐report (self‐diagnosis) of hand dermatoses or eczema ( ‘Have you had…?’ ) or a diagnosis based on a symptom list (symptom‐based diagnosis). In the validations, clinical hand eczema has been diagnosed in 54–94% of the respondents reporting hand eczema/dermatitis in questionnaire studies (‘Have you had…?’/‘Do you have…?’) (1, 2, 21, 26, 27, 30, 31).…”
Section: Questionnaire Methods For Assessing Hand Dermatitismentioning
confidence: 99%